The Effect Of Financial Ratio and Macroeconomic On Financial Distress On Property, Real Estate And Building Construction Companies Listed On The Indonesian Stock Exchange 2015-2019 - Dwi Ajeng Nadia; Andewi Rokhmawati; Fitri Fitri (Universitas Riau, 2022)
This study aims to examine the effect of financial ratios and macroeconomic on financial distress. Financial ratios are assessed using the ROE, DER, CR, SG, CFFO proxies and macroeconomic proxies are inflation, exchange rates, BI rate, GDP and financial distress measured by the springate model. The data used in this study is secondary data in the form of annual reports from 2015-2019 obtained from the Indonesian Stock Exchange website or www.idx.co.id and Bank Indonesia or www.bi.go.id and the Central Bureau of Statistics or www.bps.go.id. The population in this study amounted to 53 property, real estate and building construction companies listed on the Indonesian Stock Exchange with a sampling technique using purposive sampling obtained as many as 40 companies. Hypothesis testing in this study used logistic regression analysis with the help of the SPSS application. The results obtained indicate that ROE, CR, SG, CFFO, Inflation has a significant negative effect on financial distress. DER, BI rate, exchange rate have a significant positive effect on financial distress. While, GDP has no significant effect on financial distress.